Analisis Islamic corporate governance dan pengungkapan islamic social reporting terhadap kinerja keuangan bank umum syariah dengan pendekatan moderated regression analysis - Wibisana, Devangesty Enggar; Nila Saadati (Journal of Accounting and Digital Finance, 2022)
This study aims to determine the effect of Islamic Corporate Governance and Islamic Social Reporting on the performance of the quantity with the company's size as a moderation variable on the 2014-2019 bus. This quantitative research uses secondary data in the form of panel data. The sample of this study was 11 buses in 2014-2019 with annual data, so the number of samples used was 66. The method used was moderated regression analysis. The results of this study show that Islamic Corporate Governance has a significant negative effect on financial performance. The Islamic Social Reporting variable has no effect. The company's size as a variable moderation of Islamic Corporate Governance on financial performance has a positive effect, while the size of the company does not moderate Islamic Social Reporting on financial performance.